(untitled) (International Journal of Engineering and Computer Science, 2014)
The problems revolving around the educational system up till now has not or cannot be completely solved, however these can still be minimized/reduced to enhance successful teaching-learning process. There are numerous problems militating against a successful teaching-learning process, however this is limited to the ones observed in AjayiCrowther University. One of the problems identified is students’ inability to ask questions in class and which is identified as being caused by students’ bad diction or lack of boldness or courage. In this paper, we propose a system that will help to eradicate this problem by integrating a chat module into the schools website to allow students engage in remote communication with either their lecturers or other students. The system will have an integrated website that will provide students with self-study objects (such as the e-books, tutorial videos and audios) and object modules such as the chat facility.